Development and validation of educational technology for venous ulcer care - Jéssica Lima Benevides; Janaina Fonseca Victor Coutinho; Liliane Chagas Pascoal; Emanuella Silva Joventino; Mariana Cavalcante Martins; Fabiane do Amaral Gubert; Allana Mirella Alves (SciELO, 2016)
Abstract OBJECTIVE To develop and validate an educational technology venous ulcers care. METHOD Methodological study conducted in five steps: Situational diagnosis; literature review; development of texts, illustrations and layout; apparent and content validity by the Content Validity Index, assessment of Flesch Readability Index; and pilot testing. RESULTS The developed technology was a type of booklet entitled Booklet for Venous Ulcers Care, consisting of seven topics: Diet and food intake, walking and light exercise, resting with elevated leg, bandage care, compression therapy, family support, and keeping healthy habits. The apparent validity revealed minimal agreement of 85.7% in the clarity and comprehensibility. The total content validity index was 0.97, the Flesch Readability Index was 75%, corresponding to the reading "fairly easy". The pilot test showed that 100% of people with venous ulcers evaluated the text and the illustrations as understandable, as appropriate. CONCLUSION The educational technology proved to be valid for the appearance and content with potential for use in clinical practice.